(untitled) (Herald of Journalism, 2020)
The scientific article describes the formation of the theory of industry journalism, which is currently one of the current problems – sports journalism. The purpose of the article is Describe the lack of a theoretical base and research on media coverage of physical culture and sports, the history of this process, which in particular is an urgent requirement of today. Summarize and describe the experience of sports journalism, highlight trends in the development of sports journalism. Consideration of physical culture and sports in sports journalism of Kazakhstan as the most important aspect of society culture. Definition of the role of sports journalism of Kazakhstan, as well as its place in the international information space, peculiarities of the manifestation of the main trends in sports journalism at the national level. The scientific novelty of the article is the setting of the question in the context of a comparative- historical and structural-functional analysis of the development of the information sphere, the informa- tion space in Kazakhstan, as well as the transformation of genres – determines the novelty of scientific research. The value of the study is the study of the genre palette in sports journalism, as well as the focus of online publications on the nature of materials. The main results and conclusions of the article are a description of the development of sports jour- nalism in Kazakhstan, which took place in direct dependence on the development of the material and technical base of sports in the country, the development of the sports movement, influence from the state and society. Provide sports information as a special phenomenon of sociocultural and informational ac- tivity. The typology of sports media is analyzed, the specifics of the work of a sports journalist in modern conditions are explained.